Effect of topical insulin on cutaneous wound healing in rats with or without acute diabetes - ERCAN, FERİHA; RABUŞ, ŞULE (WILEY-BLACKWELL PUBLISHING, INC, 2010)
Background. Diabetes is a condition known even in its early stages to impair the normal course of wound healing, thus leading to chronic wounds. The role of insulin in the regulation of energy metabolism, protein synthesis, cell differentiation and growth suggests that this hormone could also play an essential role in regulation of wound healing. Aim. To determine the effects of topical insulin administration on wound healing in rats with or without acute diabetes. Methods. This study was conducted using four groups of male Sprague-Dawley rats: (i) nondiabetic rats receiving topical insulin (n = 7), (ii) nondiabetic rats receiving topical sterile water (n = 7), (iii) diabetic rats receiving topical insulin (n = 7) and (iv) diabetic rats receiving topical sterile water (n = 7). Wound healing was assessed by wound contraction rate, complete epithelialization time and histological results. Results. Topical insulin enhanced wound healing by shortening the time needed for complete epithelialization in both the nondiabetic and acute diabetic groups. The histological observations supported the planimetric results in both groups. Conclusions. This study revealed that topical insulin application to cutaneous wounds accelerates wound healing in rats with or without acute diabetes.
Keywords: HUMAN EPIDERMAL-KERATINOCYTES; HUMAN-SKIN FIBROBLASTS; GROWTH-FACTOR; STIMULATION; MIGRATION; BURN